New policy challenges for European multinationals - Tulder, Rob van; Verbeke, Alain; Voinea, Liviu (Progress in international business research, 2012)
This volume takes stock of the latest international business research on the relationship between European multinational enterprises (MNEs) and their policy environment. The volume brings together a variety of scholarly contributions from an European perspective. European MNEs were amongst the earliest to internationalize and many now command globally dispersed operations. European MNEs pioneered the multi-centric organizational form, which can be interpreted in part as an effort to address the policy challenges facing these firms in environments fraught with natural and government-imposed market imperfections. The volume covers four dimensions of MNE corporate strategy in the face of complex policy environments: 1. Corporate strategic responses to national policy institutions 2. Pro-active institution-oriented strategies 3. Dynamics of international business-government relations; 4. Corporate strategies in turbulent times.